2019
DOI: 10.3389/fimmu.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Glycan-Specific Natural Antibodies Repertoire in GalT-KO Mice Is Determined by Gut Microbiota

Abstract: Gut commensal bacteria are known to have a significant role in regulating the innate and adaptive immune homeostasis. Alterations in the intestinal microbial composition have been associated with several disease states, including autoimmune and inflammatory conditions. However, it is not entirely clear how commensal gut microbiota modulate and contribute to the systemic immunity, and whether circulating elements of the host immune system could regulate the microbiome. Thus, we have studied the diversity and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 59 publications
(75 reference statements)
1
41
0
Order By: Relevance
“…2a-d). Both mice contained circulating anti-glycan IgM antibodies in their serum prior to immunization, as has been observed previously 40,41 . The repertoire of these IgM antibodies for both animals analyzed were highly correlated (r = 0.88), and were against a variety of blood group and Lewis antigens to name a few ( Fig.…”
Section: Resultssupporting
confidence: 75%
“…2a-d). Both mice contained circulating anti-glycan IgM antibodies in their serum prior to immunization, as has been observed previously 40,41 . The repertoire of these IgM antibodies for both animals analyzed were highly correlated (r = 0.88), and were against a variety of blood group and Lewis antigens to name a few ( Fig.…”
Section: Resultssupporting
confidence: 75%
“…Our study fits with previous observations that indirectly suggested that gut microbiome was the main source of production of the Gal antigen (18) resulting in the rise of the anti-Gal within the first year of life. Interestingly, in α1,3GT-KO mice, modifications of gut microbiome followed during the first months of life were related to anti-Gal Ab levels (31). However, our estimation likely underestimates the actual proportion of the microbiota able to produce the Gal antigen as also suggested by the presence of anti-Gal antibodies in most of the adult individuals tested.…”
Section: Discussionmentioning
confidence: 74%
“…Instead, it performs exhaustive pairwise alignment on all sequences using dynamic programming without statistical approximations, and hence avoids the need for ensemble analysis that may be required when using other approximate tools that may have sensitivity/specificity tradeoffs in pursuing or calculating alignments. Especially for lower alignment identities, general-purpose techniques designed for speedy approximate alignment (read mappers, classifiers) are not applicable, as they use approximations that are reasonable for short-read mapping but not lower-identity alignment (under some metrics of precision/accuracy/sensitivity/recall) (29)(30)(31). Because we are looking for potentially divergent sequences, we selected BURST over high-speed metagenomic classifiers such as MEGAN, MEGAN-LR (31) or Kraken (29) despite the increased computational cost.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Pure polysaccharides are considered to be relatively weak antigens in mammals when used as immunogens alone or used independently of their expression on a microbe, as such free polysaccharides are often T cell-independent and generate a biased IgM response 6 – 8 . Some zwitterionic polysaccharides can directly induce T cell-dependent IgG anti-carbohydrate antibodies 9 , 10 , and ACAs to the gut microbiota have been identified 11 , 12 . Regardless of whether responses are T cell-independent or -dependent, the presence of a diverse array of IgG antibodies to carbohydrates has been observed in many preparations of IVIG, purified IgG products prepared from pooled human plasma and made available through many different commercial sources 13 .…”
Section: Introductionmentioning
confidence: 99%